2019
DOI: 10.15244/pjoes/104461
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield and Nutritional Performance of Sweet Sorghum and Legumes in Sole and Intercropping Influenced by Type of Legume, Nitrogen Level and Air Quality

Abstract: Sweet sorghum is a drought-tolerant cereal widely grown as pure stand in water-scarce areas. In the context of ongoing climate change, some agronomic adjustments are required for sustainable food production. Intercropping sweet sorghum with mungbean and soybean was assessed under three N levels (30, 60, 120 kg ha-1) and two types of air quality environments (charcoal filtered air and ambient air). Grain yield of sweet sorghum was significantly (P≤0.001) reduced in intercropping with mungbean (4.5 t ha-1), but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…The highest grain yield was obtained (2779.8 kg/ha) in the pure culture of sorghum and it was statistically significant in comparison to sorghum-legume (1953.4 kg/ha) intercrop [36] . The results were in line with an experiment performed by Arshad and Ranamukhaarachchi (2012) in which plant height of sorghum was reduced in sorghum-mungbean cropping system in comparison to sole culture [37] . This reduction in grain yield was due to the reduced number of grains panicle-1of sorghum that resulted in the competition of growth resources (air, space moisture, and nutrients) in sorghum-legume cropping system compared with sole sorghum [38] .…”
Section: Table 1 Yield Components Of Mungbean As Affected By Sole And...supporting
confidence: 88%
“…The highest grain yield was obtained (2779.8 kg/ha) in the pure culture of sorghum and it was statistically significant in comparison to sorghum-legume (1953.4 kg/ha) intercrop [36] . The results were in line with an experiment performed by Arshad and Ranamukhaarachchi (2012) in which plant height of sorghum was reduced in sorghum-mungbean cropping system in comparison to sole culture [37] . This reduction in grain yield was due to the reduced number of grains panicle-1of sorghum that resulted in the competition of growth resources (air, space moisture, and nutrients) in sorghum-legume cropping system compared with sole sorghum [38] .…”
Section: Table 1 Yield Components Of Mungbean As Affected By Sole And...supporting
confidence: 88%
“…This method is a feasible harvesting practice ( 11 , 12 ). Sorghum intercropping with some legumes has many economic returns ( 13 15 ), and the sorghum ratooning practice also has several advantages, such as no need for new seed and land preparation, covering of time of sowing, and high grain yield and quality ( 12 ). Zhou et al ( 16 ) reported that sorghum ratoon crop has high contents of starch, protein, and tannin and low fat content after application of nitrogen fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that, their high demand for nutrients and water must not overlap to minimize interspecific competition. Several reports used different legume species to grow with the cereal, such as faba bean (Bechtaoui et al, 2019a;Zhang et al, 2019), cowpea (Takim, 2012), soybean (Baghdadi et al, 2016;Arshad et al, 2020), and mungbean (Arshad et al, 2020). The ability to intercrop to reduce erosion and improve soil fertility makes intercropping a wellrecommended cropping system.…”
Section: Discussionmentioning
confidence: 99%